PELATIHAN PENCATATAN KEUANGAN DAN PEMAHAMAN PAJAK FINAL UMKM BAGI PELAKU USAHA MIKRO - Eka Putra, Wirmie; Dahlia; Aprilia Murnidayanti, Scheilla; Heriyani, Heriyani; Sukmawati, Aegisia; Nanda Utami , Febby (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2025)
This community service activity aims to enhance the understanding of Micro, Small, and Medium Enterprises (MSMEs) in Kumpeh Ulu District, Muaro Jambi Regency regarding basic financial recordkeeping and tax obligations, particularly the Final Income Tax (PPh Final). The lack of knowledge and skills in managing business finances often hinders MSME growth, including fulfilling tax obligations in accordance with regulations. The implementation method was carried out through face-to-face training, interactive discussions, and financial recording simulations using a simple format that can be directly applied. The results of the activity showed an 80% increase in participants’ understanding of financial recordkeeping and final tax obligations, based on pre-test and post-test assessments. This training is expected to help micro-entrepreneurs manage their finances more systematically and comply with tax regulations.